Registry of Older South Australians (ROSA): framework and plan. Issue 6 (19th June 2019) - Inacio, Maria C; Bray, Sarah Catherine Elizabeth; Whitehead, Craig; Corlis, Megan; Visvanathan, Renuka; Evans, Keith; Griffith, Elizabeth C; Wesselingh, Steve L
Abstract : Introduction: Australia's ageing population puts significant demands on the aged care and healthcare sectors. To monitor the provision of aged care and healthcare services to older people, each government body has an individual data collection system. Together these systems can be the basis for creating the evidence necessary to support future allocation of resources for our ageing community. The Registry of Older South Australians (ROSA) is a cross-sector multidisciplinary (ie, aged care and healthcare) platform built to address the challenges of monitoring people in aged care settings. This protocol describes the ROSA's framework and plans. Methods and analysis: A registry to capture 16 000 South Australians/year undergoing an aged care eligibility assessment was designed. ROSA will contain information captured by the Commonwealth and South Australian state Health Authority, linked by two data integrating authorities, and housed on a secured data platform. ROSA will contain information on the sociodemographic, health, function, psychological, social, home and safety assessment and concerns characteristics, aged care services, general health services, and mortality of people receiving aged care services. Registered participants will be prospectively monitored until their death and yearly updates of their aged care and healthcare services information will be added to the registry. Ethics and dissemination: ROSA will longitudinally monitor the services provided to a population that puts costly demands on the state healthcare and aged care systems, identify unwanted variation, and underpin future research. ROSA's expected outputs include an annual report, a research agenda that focuses on high burden conditions and potentially economically impactful questions, educational materials, and risk profiling tools. ROSA was approved by the South Australian Department for Health and Ageing HREC (HREC/17/SAH/125) and the Australian Institute of Health and Welfare HREC (EO2018/2/429).